Physico-chemical and Phyto-chemical Standardization of Gul-e- Banafshah (Flowers of Viola odorata Linn.) (Bangladesh Journal of Medical Science, 2026)
Background Banafshah, a powerful Unani medicine, needs to be standardized in order to maintain and evaluate its quality and safety and achieve the intended therapeutic effect. As a result, the perfect monograph that establishes its authenticity, quality, safety, and reproducibility will be prepared. This study investigates the phytochemical, physicochemical and pharmacognostic characteristics of Banfashah as well as their Total phenolic content. Aim The goal of the project is to compile the perfect Banafshah monograph. Methodology The WHO’s criteria were followed in the physical-chemical and preliminary phytochemical investigations. Result The powdered Banafshah was gritty, Yellowish brown in color, Slightly aromatic, Slightly pungent and bitter, and pleasant. The results showed that the total ash, acid insoluble ash, water soluble ash, weight loss after drying, and pH (1% and 10% solution) were, in order, 11.196±0.113, 3.126±0.017, 2.336±0.121, 12.366± 0.154,7.12±0.062, and6.01±0.060respectively. The hydroalcoholic extract had a lower TPC value of 12.894±0.513, indicating that the aqueous extract contains a higher concentration of phenolic compounds. The total phenolic content of the aqueous extract was found to be 23.063±0.646. The results of the phytochemical screening showed the presence of volatile oil, alkaloids, proteins, carbohydrates, phenols, terpenes, and glycosides, including cardiac glycosides. TLC spots in different solvent systems have been noted in day light and UV light, based on TLC examinations of diverse drug extracts obtained in different solvent systems. Conclusion Pharmacopoeial standards could be established based on the results mentioned above. There are no comparable data sets in this regard, thus our conclusions can be used as standard for upcoming references.BJMS, Vol. 25 No. 01 January’26 Page : 62-67